2014
DOI: 10.1021/ci500253q
|View full text |Cite
|
Sign up to set email alerts
|

Discovering New Agents Active against Methicillin-Resistant Staphylococcus aureus with Ligand-Based Approaches

Abstract: To discover new agents active against methicillin-resistant Staphylococcus aureus (MRSA), in silico models derived from 5451 cell-based anti-MRSA assay data were developed using four machine learning methods, including naïve Bayesian, support vector machine (SVM), recursive partitioning (RP), and k-nearest neighbors (kNN). A total of 876 models have been constructed based on physicochemical descriptors and fingerprints. The overall predictive accuracies of the best models exceeded 80% for both training and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…Recently, Ebejer et al [24] reported the comparison between the physicochemical properties of antibacterial compounds and other drugs and concluded that the percentage of compounds with TopoPSA < 120 Å 2 is 84.4% and 52.6% for marketed other drugs and antibacterial drugs, respectively, which is in agreement with our previously stablished rule [21]. Wang et al developed in silico classification models derived from 5451 cell-based anti-MRSA assay data using four machine learning (ML) methods, including naïve Bayesian, support vector machine (SVM), recursive partitioning, and k -nearest neighbors [25]. The best model was employed for the virtual screening of anti-MRSA compounds, which were validated by cell-based assays with three types of highly resistant MRSA strains and a total of 12 new anti-MRSA agents were experimentally confirmed by the authors [25].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Recently, Ebejer et al [24] reported the comparison between the physicochemical properties of antibacterial compounds and other drugs and concluded that the percentage of compounds with TopoPSA < 120 Å 2 is 84.4% and 52.6% for marketed other drugs and antibacterial drugs, respectively, which is in agreement with our previously stablished rule [21]. Wang et al developed in silico classification models derived from 5451 cell-based anti-MRSA assay data using four machine learning (ML) methods, including naïve Bayesian, support vector machine (SVM), recursive partitioning, and k -nearest neighbors [25]. The best model was employed for the virtual screening of anti-MRSA compounds, which were validated by cell-based assays with three types of highly resistant MRSA strains and a total of 12 new anti-MRSA agents were experimentally confirmed by the authors [25].…”
Section: Introductionsupporting
confidence: 78%
“…Following our previous work that modeling the anticancer activity against HCT116 [37], the current results suggest as well that the chemoinformatics QSAR approach relying on a ligand-based methodology either based on the molecular structures or the NMR spectra, corroborated with an experimental approach, could be used to predict new inhibitory compounds against MRSA. To our knowledge, the QSAR regression model developed here, approach A, is the largest study ever performed with regard both to the number of compounds involved and to the number of structural families involved in the modeling of the antibacterial activity against MRSA [19,20,25]. The NMR QSAR classification model, approach B, was extended to a high number of samples containing additional 45 pure compounds and therefore the overall predictability accuracies (Q) were improved as compared with those obtained in our previously work [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al chose an NB classifier from over 800 ML models that utilized four distinct techniques because it performed the best on external testing and gave favorable fragments. When using this classifier on a novel compound database, 56 hits were found after filtering, and in vitro assays deemed 12 of them as significantly active [42]. Jang et al used an NB classifier as a crucial step in their drug discovery workflow, which produced new and structurally diverse hits for mGlu1 receptor inhibitors [21].…”
Section: Machine Learning Methods For Virtual Screeningmentioning
confidence: 99%
“…Student's t-test was used to calculate the p-value of all the properties of active and inactive compounds. 32 The p-value and the correlation coefficients between the a NLG8189 was used as the positive control. properties and inhibitory activity were calculated using SPSS 13.0.…”
Section: Diversity Analysismentioning
confidence: 99%